Molecular detection of Rickettsia in fleas from micromammals in Chile - Moreno Salas, Lucila (2020)
Background: Rickettsial diseases are considered important in public health due to their dispersal capacity determined by the particular characteristics of their reservoirs and/or vectors. Among the latter, fleas play an important role, since the vast majority of species parasitize wild and invasive rodents, so their detection is relevant to be able to monitor potential emerging diseases. The aim of this study was to detect, characterize, and compare Rickettsia spp. from the fleas of micromammals in areas with different human population densities in Chile. Methods: The presence of Rickettsia spp. was evaluated by standard polymerase chain reaction (PCR) and sequencing in 1315 fleas collected from 1512 micromammals in 29 locations, with different human population densities in Chile. A generalized linear model (GLM) was used to identify the variables that may explain Rickettsia prevalence in fleas. Results: DNA of Rickettsia spp. was identified in 13.2% (174 of 1315) of fleas tested. Fifteen flea species were found to be Rickettsia-positive. The prevalence of Rickettsia spp. was higher in winter, semi-arid region and natural areas, and the infection levels in fleas varied between species of flea. The prevalence of Rickettsia among flea species ranged between 0–35.1%. Areas of lower human density showed the highest prevalence of Rickettsia. The phylogenetic tree showed two well-differentiated clades with Rickettsia bellii positioned as basal in one clade. The second clade was subdivided into two subclades of species related to Rickettsia of the spotted fever group. Conclusions: To our knowledge, this is the first report of the occurrence and molecular characterization of Rickettsia spp. in 15 flea species of micromammals in Chile. In this study, fleas were detected carrying Rickettsia DNA with zoonotic potential, mainly in villages and natural areas of Chile. Considering that there are differences in the prevalence of Rickettsia in fleas associated with different factors, more investigations are needed to further understand the ecology of Rickettsia in fleas and their implications for human health.[Figure not available: see fulltext.]